Early detection versus primary prevention in the PLCO flexible sigmoidoscopy screening trial: Which has the greatest impact on mortality?. Issue 24 (4th October 2017) - Doroudi, Maryam; Schoen, Robert E.; Pinsky, Paul F.
Abstract : BACKGROUND: Screening for colorectal cancer (CRC) with flexible sigmoidoscopy (FS) has been shown to reduce CRC mortality. The current study examined whether the observed mortality reduction was due primarily to the prevention of incident CRC via removal of adenomatous polyps or to the early detection of cancer and improved survival. METHODS: The Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial randomized 154, 900 men and women aged 55 to 74 years. Individuals underwent FS screening at baseline and at 3 or 5 years versus usual care. CRC‐specific survival was analyzed using Kaplan‐Meier curves and proportional hazards modeling. The authors estimated the percentage of CRC deaths averted by early detection versus primary prevention using a model that applied intervention arm survival rates to CRC cases in the usual‐care arm and vice versa. RESULTS: A total of 1008 cases of CRC in the intervention arm and 1291 cases of CRC in the usual‐care arm were observed. Through 13 years of follow‐up, there was no significant difference noted between the trial arms with regard to CRC‐specific survival for all CRC (68% in the intervention arm vs 65% in the usual‐care arm; P =.16) or proximal CRC (68% vs 62%, respectively; P = .11) cases; however, survival in distal CRC cases was found to be higher in the intervention arm compared with the usual‐care arm (77% vs 66%; P <.0001). Within each arm, symptom‐detected cases had significantly worse survival compared with screen‐detected cases. Overall, approximately 29% to 35% of averted CRC deaths were estimated to be due to early detection and 65% to 71% were estimated to be due to primary prevention. CONCLUSIONS: CRC‐specific survival was similar across arms in the PLCO trial, suggesting a limited role for early detection in preventing CRC deaths. Modeling suggested that approximately two‐thirds of avoided deaths were due to primary prevention. Future CRC screening guidelines should emphasize primary prevention via the identification and removal of precursor lesions. Cancer 2017;123:4815‐22 . © 2017 American Cancer Society . Abstract : Colorectal cancer‐specific survival appears to be similar across treatment arms in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial, suggesting a limited role for early detection in the prevention of colorectal cancer deaths. Modeling suggests that approximately two‐thirds of averted deaths are due to primary prevention. See also pages 4767‐9.